EXAMPLE 4 Solve a logarithmic equation Solve log (4x – 7) = log (x + 5). 5 5 log (4x – 7) = log (x + 5). 5 5 4x – 7 = x + 5 3 x – 7 = 5 3x = 12 x = 4 Write.

Slides:



Advertisements
Similar presentations
( ) EXAMPLE 3 Solve ax2 + bx + c = 0 when a = 1
Advertisements

Warm-Up. One way to solve exponential equations is to use the property that if 2 powers w/ the same base are equal, then their exponents are equal. For.
EXAMPLE 4 Solve proportions SOLUTION a x 16 = Multiply. Divide each side by 10. a x 16 = = 10 x5 16 = 10 x80 = x8 Write original proportion.
EXAMPLE 4 Solve proportions SOLUTION a x 16 = Multiply. Divide each side by 10. a x 16 = = 10 x5 16 = 10 x80 = x8 Write original proportion.
Solve an equation with variables on both sides
Solve an equation by combining like terms
EXAMPLE 1 Solve a quadratic equation having two solutions Solve x 2 – 2x = 3 by graphing. STEP 1 Write the equation in standard form. Write original equation.
EXAMPLE 1 Solve a simple absolute value equation Solve |x – 5| = 7. Graph the solution. SOLUTION | x – 5 | = 7 x – 5 = – 7 or x – 5 = 7 x = 5 – 7 or x.
Solve an absolute value equation EXAMPLE 2 SOLUTION Rewrite the absolute value equation as two equations. Then solve each equation separately. x – 3 =
EXAMPLE 2 Using the Cross Products Property = 40.8 m Write original proportion. Cross products property Multiply. 6.8m 6.8 = Divide.
Solve an equation using subtraction EXAMPLE 1 Solve x + 7 = 4. x + 7 = 4x + 7 = 4 Write original equation. x + 7 – 7 = 4 – 7 Use subtraction property of.
Standardized Test Practice
Solve a linear-quadratic system by graphing
EXAMPLE 1 Solve a linear-quadratic system by graphing Solve the system using a graphing calculator. y 2 – 7x + 3 = 0 Equation 1 2x – y = 3 Equation 2 SOLUTION.
EXAMPLE 1 Collecting Like Terms x + 2 = 3x x + 2 –x = 3x – x 2 = 2x 1 = x Original equation Subtract x from each side. Divide both sides by x2x.
Standardized Test Practice
EXAMPLE 3 Solve an equation by factoring Solve 2x 2 + 8x = 0. 2x 2 + 8x = 0 2x(x + 4) = 0 2x = 0 x = 0 or x + 4 = 0 or x = – 4 ANSWER The solutions of.
Standardized Test Practice
Solve a radical equation
Solve an equation with an extraneous solution
CH. 8.6 Natural Logarithms. Write 2 ln 12 – ln 9 as a single natural logarithm. 2 ln 12 – ln 9 = ln 12 2 – ln 9Power Property = lnQuotient Property 12.
5.4 Exponential and Logarithmic Equations Essential Questions: How do we solve exponential and logarithmic equations?
Exponential and Logarithmic Equations
7-5 Logarithmic & Exponential Equations
Take a logarithm of each side
4.6 Solve Exponential and Logarithmic Equations
7.6 – Solve Exponential and Log Equations
Solve an equation with an extraneous solution
( ) EXAMPLE 3 Standardized Test Practice SOLUTION 5 x = – 9 – 9
EXAMPLE 2 Rationalize denominators of fractions Simplify
Solve a logarithmic equation
Solve an equation by combining like terms EXAMPLE 1 8x – 3x – 10 = 20 Write original equation. 5x – 10 = 20 Combine like terms. 5x – =
Rational Equations Section 8-6.
Solve a two-step inequality EXAMPLE 1 3x – 7 < 8 Write original inequality. 3x < 15 Add 7 to each side. x < 5 Divide each side by 3. ANSWER The solutions.
Example 1A Solve the equation. Check your answer. (x – 7)(x + 2) = 0
For b > 0 and b ≠ 1, if b x = b y, then x = y. S OLVING E XPONENTIAL E QUATIONS If two powers with the same base are equal, then their exponents must be.
Add or subtract with like denominators
Solve an equation using addition EXAMPLE 2 Solve x – 12 = 3. Horizontal format Vertical format x– 12 = 3 Write original equation. x – 12 = 3 Add 12 to.
EXAMPLE 1 Solve by equating exponents Rewrite 4 and as powers with base Solve 4 = x 1 2 x – 3 (2 ) = (2 ) 2 x – 3x – 1– 1 2 = 2 2 x– x + 3 2x =
Example 1 Solving Two-Step Equations SOLUTION a. 12x2x + 5 = Write original equation. 112x2x + – = 15 – Subtract 1 from each side. (Subtraction property.
Use the substitution method
Solve Linear Systems by Substitution January 28, 2014 Pages
Solve Linear Systems by Substitution Students will solve systems of linear equations by substitution. Students will do assigned homework. Students will.
EXAMPLE 2 Take a logarithm of each side Solve 4 = 11. x 4 = 11 x log 4 = log 11 x 4 4 log 4 x = 11 x = log 11 log 4 x 1.73 SOLUTION Write original equation.
Holt McDougal Algebra Exponential and Logarithmic Equations and Inequalities Solve logarithmic equations. Objectives.
7.6A Solving Exponential and Logarithmic Equations Algebra II.
3.4 Solving Exponential and Logarithmic Equations.
Example 1 Solve Using Equal Powers Property Solve the equation. a. 4 9x = – 4 x x23x = b. Write original equation. SOLUTION a. 4 9x 5 42.
Solve the equation. 1. = 4 x x(x – 4) = 3(x – 4) + x ANSWER 10
Substitution Method: Solve the linear system. Y = 3x + 2 Equation 1 x + 2y=11 Equation 2.
For b > 0 and b  1, if b x = b y, then x = y.
Rewrite a linear equation
Ch. 8.5 Exponential and Logarithmic Equations
1. Add: 5 x2 – 1 + 2x x2 + 5x – 6 ANSWERS 2x2 +7x + 30
EXAMPLE 2 Rationalize denominators of fractions Simplify
3.4 Quick Review Express In 56 in terms of ln 2 and ln 7.
( ) EXAMPLE 3 Standardized Test Practice SOLUTION 5 x = – 9 – 9
Find the least common multiple for each pair.
Find the least common multiple for each pair.
7.6 Solve Exponential and Logarithmic Equations
Solve an equation by combining like terms
EXAMPLE 4 Standardized Test Practice SOLUTION
WARMUP Lesson 7.6, For use with pages
Logarithmic and Exponential Equations
You can find the roots of some quadratic equations by factoring and applying the Zero Product Property. Functions have zeros or x-intercepts. Equations.
Solving Multi-Step Equations
Solve an inequality using subtraction
For b > 0 and b ≠ 1, if b x = b y, then x = y.
Definition of logarithm
EXAMPLE 4 Solve proportions Solve the proportion. ALGEBRA a x 16
Presentation transcript:

EXAMPLE 4 Solve a logarithmic equation Solve log (4x – 7) = log (x + 5). 5 5 log (4x – 7) = log (x + 5) x – 7 = x x – 7 = 5 3x = 12 x = 4 Write original equation. Property of equality for logarithmic equations Subtract x from each side. Add 7 to each side. Divide each side by 3. The solution is 4. ANSWER SOLUTION

EXAMPLE 4 Solve a logarithmic equation Check: Check the solution by substituting it into the original equation. Write original equation. Substitute 4 for x. Solution checks. (4x – 7) = (x – 5) log 5 5 (4 4 – 7) = (4 + 5) ? log = 9 log 5 5

EXAMPLE 5 Exponentiate each side of an equation 5x – 1 = 64 5x = 65 x = 13 SOLUTION Write original equation. Exponentiate each side using base 4. Add 1 to each side. Divide each side by 5. Solve (5x – 1)= 3 log 4 4 log 4 (5x – 1) = 4 3 (5x – 1)=(5x – 1)= 3 log 4 b = x log b x The solution is 13. ANSWER

EXAMPLE 5 Exponentiate each side of an equation log 4 (5x – 1) = (5 13 – 1) = 64 log 4 4 Check: log 4 Because 4 = 64, 64= 3. 3

EXAMPLE 6 Standardized Test Practice SOLUTION log 2x + log (x – 5) = 2 log [2x(x – 5)] = 2 2x(x – 5) = 100 Write original equation. Product property of logarithms Exponentiate each side using base 10. Distributive property 10 = 10 log 2 [2x(x – 5)]

EXAMPLE 6 Standardized Test Practice x – 5x – 50 = 0 2 (x – 10)(x + 5) = 0 x = 10 or x = – 5 Check: Check the apparent solutions 10 and – 5 using algebra or a graph. Write in standard form. Divide each side by 2. Factor. 2x – 10x – 100 = 0 2 2x – 10x = Zero product property b = x log b x Algebra: Substitute 10 and 25 for x in the original equation.

EXAMPLE 6 log 2x + log (x – 5) = 2 Standardized Test Practice log 20 + log 5 = 2 log 100 = 2 2 = 2 log 2x + log (x – 5) = 2 log [2(–5)] + log (–5 – 5) = 2 log (–10) + log (–10) = 2 Because log (–10) is not defined, –5 is not a solution. So, 10 is a solution. log (2 10) + log (10 – 5) = 2

EXAMPLE 6 Standardized Test Practice Graph: Graph y = log 2x + log (x – 5) and y = 2 in the same coordinate plane. The graphs intersect only once, when x = 10. So, 10 is the only solution. The correct answer is C. ANSWER

GUIDED PRACTICE for Examples 4, 5 and 6 Solve the equation. Check for extraneous solutions. 7. ln (7x – 4) = ln (2x + 11) SOLUTION Write original equation. ln (7x – 4) = ln (2x + 11) 7x – 4 = 2x x – 2x = 11 – 4 5x = 15 x = 3 The solution is 3. ANSWER Property of equality for logarithmic equations Divide each side by 5.

GUIDED PRACTICE for Examples 4, 5 and 6 Solve the equation. Check for extraneous solutions. 8. log (x – 6) = 5 2 SOLUTION log (x – 6) = 5 2 Write original equation. 2log (x – 6) = x – 6 = 32 x = x = 38 The solution is 38. ANSWER Exponentiate each side using base 2. b = x log b x Add 6 to each side.

GUIDED PRACTICE for Examples 4, 5 and 6 9. log 5x + log (x – 1) = 2 Solve the equation. Check for extraneous solutions. SOLUTION log 5x + log (x – 5) = 2 log [5x(x – 1)] = 2 5x(x – 1) = 100 Write original equation. Product property of logarithms Exponentiate each side using base 10. Distributive property 10 = 10 log 2 [5x(x – 1)]

GUIDED PRACTICE for Examples 4, 5 and 6 x – 5x + 4x – 20 = 0 2 (x – 5)(x +4) = 0 x = 5 or x = – 4 Factor. x – x – 20 = 0 2 x – x = 20 2 Zero product property b = x log b x x – x = x(x – 5)+4(x – 5) = 0 Check: Check the apparent solutions 5 and – 4 using algebra or a graph.

GUIDED PRACTICE for Examples 4, 5 and 6 Algebra: Substitute – 4 and 5 for x in the original equation. log 5x + log (x – 1) = 2 log –20 + log –5 = 2 log 100 = 2 2 = 2 log 5x + log (5x – 1) = 2 log [5(5)] + log (5(5) –1) = 2 log 25 + log 24 = 2 log5(– 4 ) + log (– 4 –1) = 2 log 600 = = 2 So, – 4 is a solution. ANSWER

GUIDED PRACTICE for Examples 4, 5 and 6 Solve the equation. Check for extraneous solutions. SOLUTION 10. log (x + 12) + log x =3 4 4 log (x + 12) + log x = log [(x + 12) x] = 3 4 log (x + 12 x) = 3 2 x + 12 x = Exponentiate each side using base 4. 4 log (x + 12 x) 2 4 = 4 3

GUIDED PRACTICE for Examples 4, 5 and 6 (x – 4)(x +4) = 0 x = 4 or x = – 4 x + 12x – 64 = 0 2 x(x +4) – 4(x +4) = 0 x + 12 x = 64 2 x +16x – 4x – 64 = 0 2 Factor. Zero product property Check: Check the apparent solutions 4 and – 4 using algebra or a graph.

GUIDED PRACTICE for Examples 4, 5 and 6 Algebra: Substitute 4 and – 4 for x in the original equation. So, 4 is a solution.ANSWER log (4 + 12) + log 4 = log = 3 4 log log 4 = 3 4 log 16 = 2 log 16 log 4 = = 2 log (– ) + log – 4 = log 8 – 1= 3 4 log – 4 = 3 log 8 log 4 = 4 4 log 8 = = 4